ACRODYNIA AS A REASON OF HYPERTENSIVE CRISES IN 2-YEAR OLD GIRL. (June 2018) - Obrycki, L.; Litwin, M.
Abstract : Objective: We present a case of 2-year old girl referred to our clinic to evaluate diagnosis of hypertension and nephrocalcinosis. In the course of diagnosis it turned out that that the reason for the occurrence of symptoms was mercury poisoning (acrodynia). Design and method: Previously healthy 2-year old girl was admitted to the Department of Nephrology, Kidney Transplantations and Hypertension because of recurrent attacks of sweating with painful redness of hands and feet, apathy and impaired consciousness with accompanying arterial hypertension with values up to 180/110 mmHg. The symptoms lasted since 5 months and gradually stopped. Ultrasound imaging revealed nephrocalcinosis, although renal sonography performed at 1st year of life was normal. Laboratory values were normal but blood and urine samples taken during hypertensive crises showed normal anion gap metabolic acidosis with alkaline urine (urine pH 8) and hypercalciuria. At the admission the girl was treated with enalapril and propranolol. Blood pressure values were 102/60mmHg. Results: Detailed history revealed that paroxysmal neurological symptoms (paroxysmal redness and paleness of hands and feet, sudden apathy, worse appetite and impaired consciousness) with recurrent hypertensive crises appeared 5 months earlier and were related to mercury vapor exposure during cleaning with use of vacuum cleaner the remains of crushed mercury containing thermometer. Because of suspicion of mercury intoxication, urine sample taken in the first days after exposure was analyzed and it was found that mercury concentration was significantly elevated. Conclusions: Acrodynia is a condition of pain and dusky pink discoloration in the hands and feet most often seen in children chronically exposed to heavy metals, especially mercury. Besides peripheral neuropathy and discoloration, profuse sweating, tachycardia, salivation and elevated blood pressure with hypertensive crises suggesting catecholamine excess can also occur. This is explained by the fact that mercury can block metabolism of catecholamines, e.g. epinephrine). Usually, mercury intoxication is caused by swallowing of mercury droplets by small children. However, as we present, severe intoxication leading to symptoms mimicking phaeochromocytoma can be caused by inhalation of vapor from dispersed droplets of mercury. Nephrocalcinosis can be explained by repeated bouts of hypercalciuria during hypertensive crises.